The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/suco.202200192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of replacement ratio and particle size distribution of recycled coarse aggregate on mechanical properties of concrete designed using equivalent mortar volume method

Abstract: The equivalent mortar volume (EMV) mixing method has been proposed to prepare recycled aggregate concrete (RAC) with comparable mechanical properties to those of reference natural aggregate concrete (NAC). Previous studies primarily focused on the mechanical properties of EMV concrete with a single replacement ratio of recycled coarse aggregate (RCA). This paper investigates how the mechanical properties of EMV concrete vary with the replacement ratios and particle size distributions of RCA. Five different RCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…This allows network polymer of SiO2 and Al2O3 to be formed on its surface with a lower degree of polymerization, which promotes the reaction of active components in the slurry phase, resulting in the increase in the C-S-H gel content [63]; or under the action of Ca 2+ , SO4 2− produced by the promoted hydrolysis reacts with Al2O3 to form ettringite. Therefore, heat treatment is an effective way to enhance the activity of RCP, and there was found about a 16.4% increase in activity of RCP after heat treatment at 800 • C compared to untreated [48]. Yang et al [43] found that after heat treatment at 600-800 • C, the compressive strength of concrete with 30% RCP content was 16.7-26.9% higher than that of concrete without heat treatment.…”
Section: Heat Treatmentmentioning
confidence: 99%
“…This allows network polymer of SiO2 and Al2O3 to be formed on its surface with a lower degree of polymerization, which promotes the reaction of active components in the slurry phase, resulting in the increase in the C-S-H gel content [63]; or under the action of Ca 2+ , SO4 2− produced by the promoted hydrolysis reacts with Al2O3 to form ettringite. Therefore, heat treatment is an effective way to enhance the activity of RCP, and there was found about a 16.4% increase in activity of RCP after heat treatment at 800 • C compared to untreated [48]. Yang et al [43] found that after heat treatment at 600-800 • C, the compressive strength of concrete with 30% RCP content was 16.7-26.9% higher than that of concrete without heat treatment.…”
Section: Heat Treatmentmentioning
confidence: 99%
“…The numerical method mainly uses digital image technology or parametric modeling methods to establish a simulated real model of asphalt mixtures, and then uses numerical methods for analysis and calculation [17][18][19][20]. The particle volume fraction can be large and randomly distributed, making it more suitable for studying the mechanical properties of asphalt mixtures [21][22][23][24][25]. Parametric modeling randomly generates particles of various shapes by selecting appropriate parameter ranges and, through certain shape judgments, forms a single particle that is close to the actual situation.…”
Section: Introductionmentioning
confidence: 99%